An Integrative Mesh with Dual Wettable On–Off Switch of Water/Oil. Issue 6 (27th December 2017) - Feng, Shile; Xing, Yan; Deng, Siyan; Shang, Weifeng; Li, Dan; Zhang, Miaoxin; Hou, Yongping; Zheng, Yongmei
Abstract: Smart dual selective water/oil separation mode appears on an integrative mesh, which is fabricated via combined anodic oxidation and cathodic electrode‐deposition methods. Due to the different transport directions of oil and water, oil–water mixture can be separated completely using tailor‐made device. Extrusion pressure, acting as a critical pressure that depends on liquid surface tension, substrate microstructures, and wetting properties, can be a major factor to determine the passing or blocking mode. These remarkable water/oil separation properties of the integrative mesh can bring about novel applications in fluid rectifying, microchemical reaction manipulation, advanced separation, biomedical materials, purifying industrial wastewater, etc. Abstract : Janus integrative mesh successfully achieves dual selective water or oil delivery for a high efficiency via putting oil–water mixture on both sides of janus integrative mesh simultaneously and orderly uplifting the right or left of tailor‐made device.